Automatic charging device of small -size many rotor unmanned aerial vehicle - HUI MING; GU GUANGXIANG; WANG HAOYU; ZHANG MENG; GUO PENGJING; LYU SHAOFEI (2018)
The utility model discloses an automatic charging device of small -size many rotor unmanned aerial vehicle, which comprises a mounting rack, power plug, charging circuit, first linking arm, the secondlinking arm, a first toper section of thick bamboo, a second toper section of thick bamboo, anodal connecting piece and negative electrode connection member, the fixed front that sets up at the mounting bracket of left end of first linking arm, charging circuit sets up in first linking arm, charging circuit's power input end and power plug connect, in first linking arm is stretched from the right-hand member of first linking arm to the left end of second linking arm, the right -hand member of second linking arm is upwards buckled and is formed the kink after 90 degrees, the stub end fixed connection of a kink and a first toper section of thick bamboo, charging circuit's positive output end is connected through first wire and anodal connecting piece, charging circuit's cathode output passes through second wire and